Pengembangan LKPD Bermuatan Concept Mapping Berbasis Problem Based Learning pada Materi Sistem Peredaran Darah Manusia Terhadap Pemahaman Konsep Siswa Kelas VIII SMPN 14 Pontianak Timur - Warrendayu, Crecentia T. D.; Sari, Ira Nofita; Sari, Mustika (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to develop Learner Worksheets (LKPD) containing concept mapping based on Problem Based Learning (PBL) on the material of the human circulatory system to improve the concept understanding of class VIII students at SMPN 14 East Pontianak. The research method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). The instruments used include expert validation sheets, student response questionnaires, and concept understanding tests. The data produced were analyzed qualitatively and quantitatively. The results showed that the developed LKPD was valid and feasible to use based on the assessment of material experts, media experts, and educational practitioners. Students' responses to the LKPD were also very positive, with high average scores on the aspects of ease, attractiveness, and usefulness. The application of LKPD in PBL-based learning shows a significant increase in students' concept understanding, as seen from the test results before and after using LKPD. Thus, this concept mapping and PBL-based LKPD is effective to be used as learning media to help students understand the material of human circulatory system